PROFIT ANALYSIS OF RICE (ORYZA SATIVA L.) FARMING BUSINESS AMONG SMALLHOLDER FARMERS IN NORTHWEST AGRICULTURAL ZONE OF BENUE STATE, NIGERIA - Ivom, G. A.; Ochimana, G. A.; Mando, L.; Ejembi, I. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study analyzed the profitability of rice farming among smallholder farmers in the Northwest Agricultural Zone of Benue State, Nigeria. Multistage sampling was used to select 217 rice farmers across 8 rice farming communities in 2 LGAs. Data from 216 valid questionnaires were analyzed using descriptive statistics and farm budgeting techniques, including Gross Margin and Net Farm Income. Results of the study revealed that, rice farming was dominated by male (65.74%), married (71.30%) and youthful farmers with mean age of 39.1 years, 9.2 years of experience and 1.1 hectares of land. The result further indicated that, mean total revenue per hectare was ₦1,008,866.70 against total variable cost of ₦208,941.91 and fixed cost of ₦59,048.96, resulting in an average gross margin of ₦800,078.24 and average net farm income of ₦740808.89. The study concluded that smallholder rice farming is generally profitable, though returns vary widely due to differences in input use, labour costs, and market risks. Community-based mechanization, gender-responsive land reforms and cooperative land pooling were recommended to enhance efficiency and equity.